ACE2 Promoted by STAT3 Activation Has a Protective Role in Early-Stage Acute Kidney Injury of Murine Sepsis - Chen, Tianxin; Fang, Zhendong; Zhu, Jianfen; Lv, Yinqiu; Li, Duo; Pan, Jingye (Frontiers in Medicine, 2022)
Sepsis-induced AKI (SIAKI) is associated with unacceptable morbidity and mortality. Identifying the exact onset of acute kidney injury (AKI) in sepsis is nearly impossible, leading to difficulty in recognizing the molecular mechanisms of early-stage AKI. We hypothesized that signal transducer and activator of transcription 3(STAT3) activation has a critical role in early-stage SIAKI. We established the diagnosis criteria of early-stage SIAKI and compared the biochemical and renal pathological features of early-stage AKI in mice with that in patients. We observed early-stage AKI in sepsis mice recapitulates the clinical and renal pathological features of early-stage AKI patients. The role of STAT3 signaling in early-stage AKI of sepsis mice was evaluated. The level of activated STAT3 (pSTAT3) and angiotensin-converting enzyme 2 (ACE2) in renal cortex from SIAKI mice was significantly higher than that from no AKI sepsis mice. However, apoptosis associated proteins were no differences between SIAKI and no AKI sepsis mice. Correlation analysis showed pSTAT3 level positively correlated with ACE2 expression in sepsis mice. The expressions of pSTAT3 and ACE2 in SIAKI without brush border loss (BBL) mice were higher than that in SIAKI with BBL mice. CLP with S3I201 intervention, which blocked STAT3 phosphorylation, did not lower SIAKI incidence, but deceased ACE2 expression and promote tubular injury in early-stage SIAKI. Thus, STAT3 activation may promote ACE2 expression, and then attenuate acute tubular injury in early-stage SIAKI mice. Our data indicate that ACE2 induction may offer therapeutic approaches for acute tubular injury in early-stage AKI. Keywords: